Ecology and control of Fusarium species and mycotoxins in wheat grain - Hope, Russell (Cranfield University, 2003)
This study investigated the effect of interacting environmental factors on the ecophysiology of Fusarium culmorum and F. graminearum and mycotoxin production, and potential for controlling growth and deoxynivalenol (DON) and nivalenol (NIV) production using antioxidants and essential oils on wheat grain. Two- dimensional temporal profiles of growth and DON/NIV production for F. culmorum and F. graminearum were constructed for the first time and showed that the water activity (aw, ) ranges required for growth and DON/NIV production were different in vitro and on wheat grain. Growth occurred over a wider aW range (0.9-0.99) while DON/NIV production occurred over a significantly narrower range (0.95 - 0.99 a,,, ) at both 15 and 25°C over a 40 day incubation period. Interactions between aW, temperature, and sub-optimal concentrations of fungicides had a significant impact on growth and competitiveness of F. culmorum in interspecific interactions with 5-6 other wheat grain fungi. This had an impact on both colonisation capacity in vitro and in situ and affected DON/NIV production. Interactions were complex changing with environmental or fungicide stress resulting in significant stimulation or reduction of both fungal growth and mycotoxin production. An Index of Dominance was developed to compare interspecific interactions between F. culmorum and other wheat spoilage fungi and showed that competitiveness of F. culmorum increased as temperature and a,, level approached the optimum conditions for growth and DON/NIV production. Niche overlap indices (NOI) and niche maps were developed for the first time and showed that interspecific competitiveness was closely related to the number of nutritional carbon sources shared between spoilage fungi. Hydrolytic enzyme profiles for seven different enzymes by F. culmorum, other Fusaria and spoilage fungi showed that the most competitive species produced the highest specific activity of N-acetyl-ß-D-glucosaminidase. Potential for control of Fusarium species post-harvest using 23 essential oils and 8 antioxidants was investigated. Cinnamon, clove, bay, butylated hydroxyanisole and propyl paraben (500 µg g"1) were able to significantly reduce (>90%) the colonisation of wheat grain by three Fusarium species and DON/NIV production. Bay essential oil was the most effective at controlling total fungal populations and DONNIV in naturally contaminated wheat grain.